EVALUATION OF IMPLEMENTATION MERAK-BAKAUHENI CROSSING SHIP SCHEDULE IN 2021 - Driaskoro Budi Shidarta; Surnata Surnata; Putri Febri (IWTJ : International Water Transport Journal, 2021)
Based on the results of the analysis, it is known that the problem at the Bakauheni Ferry Port is a decrease in productivity, especially passenger productivity due to the Covid-19 pandemic that entered Indonesia in March 2020. The limitation on the number of passengers from the total load capacity has caused the services provided so far to have to undergo many adjustments. in meeting the adaptation of new habits to prevent the spread of Covid-19. In the context of optimizing crossing services on the Merak - Bakauheni crossing during the Covid-19 pandemic, it is necessary to make efforts, including evaluating the schedule for fleet needs and the frequency of departures on the route. So that the implementation of the planned schedule can be carried out properly and there is a balance between the facilities that serve and the service users during the Covid-19 pandemic, it is necessary to reduce the number of ships operating according to current conditions so that they can achieve the ideal ship frequency according to the ship's load capacity. Based on this analysis, it can be concluded that the loading capacity of passengers and vehicles has decreased which affects the frequency of ships and the ideal number of ships to operate. The ideal number of ships is 22 ships/day at the regular dock and 5 ships/day at the executive dock with a ship frequency of 174 trips/day at the regular dock and 45 trips/day at the executive dock.